PENGARUH KETIDAKADILAN ORGANISASI TERHADAP PERILAKU KERJA KONTRAPRODUKTIF PADA PEKERJA MILENIAL DI INDONESIA: PENGARUH KETIDAKADILAN ORGANISASI TERHADAP PERILAKU KERJA KONTRAPRODUKTIF PADA PEKERJA MILENIAL DI INDONESIA - Putri, Reinisa Afrida; Wulandari, Jeni; Aprilia, Hani Damayanti (Jurnal Kompetitif Bisnis, 2023)
This study aims aims to determine the effects of person-organization fit and employee relations on counterproductive work behavior among millennial employees in Indonesia. This research uses the quantitative approach with explanatory research type. The sample in this study were millennial employees in Indonesia who had taken counterproductive work behavior as many as 385 respondents, which was carried out using non-probability sampling technique. Data were obtained from questionnaires distributed online using Likert scale. Data processing in this study used descriptive analysis and simple linear regression. The results of this study indicate that there is an influence of organizational injustice on counterproductive work behavior of millennial workers in Indonesia and there is also a simultaneous influence of organizational injustice on counterproductive work behavior of millennial workers in Indonesia.